Disentangling the determinants of interest and willingness-to-pay for breast cancer susceptibility testing in the general population: a cross-sectional Web-based survey among women of Québec (Canada). Issue 2 (27th February 2018) - Blouin-Bougie, Jolyane; Amara, Nabil; Bouchard, Karine; Simard, Jacques; Dorval, Michel
Abstract : Objectives: To identify common and specific individual factors that favour or impede women's interest in and willingness-to-pay (WTP) for breast cancer susceptibility testing (BCST) and to identify the most impactful factors on both outcome measures. Design and methods: This study used a self-administered cross-sectional Web-based questionnaire that included hypothetical scenarios about the availability of a new genetic test for breast cancer. Participants: French-speaking women of the general population of Québec (Canada), aged between 35 and 69 years, were identified from a Web-based panel (2410 met the selection criteria, 1160 were reached and 1031 completed the survey). Measures: The outcomes are the level of interest in and the range of WTP for BCST. Three categories of individual factors identified in the literature were used as potential explanatory factors, that is, demographic, clinical and psychosocial. Results: Descriptive statistics indicated that the vast majority of sampled women are interested in BCST (90%). Among those, more than half of them are willing-to-pay for such a test (57%). The regression models pointed out several factors associated with both outcomes (eg, age, income, family history, locus of control-powerful others) and marginal effects were used to highlight the most impactful factors for each outcome. Conclusion: The results of this study provide a proxy of the readiness of women of the general population to use and to pay for BCST. They also offer insights for developing inclusive and specific strategies to foster informed decision-making and guide the services offered by health organisations corresponding to women's preferences and needs.